Game creation to promote media and information literacy (MIL) skills in basic education teachers - Sousa, Carla; Costa, Conceição (Edições Universitárias Lusófonas, 2020)
Within the scope of GamiLearning (2015-2018), an action-research project with the aim of promoting the critical and participative dimensions of Media and Information Literacy (MIL) through collaborative experiences involving digital games, a workshop was conducted with Basic Education teachers in Portugal. The main goal of the workshop was to develop MIL skills, through the collaborative creation of digital games. To document this practice, a questionnaire was designed for teachers’ self-evaluation of their levels of MIL, their motivation to integrate the training activity, their attitudes towards videogames and their position on media education in the formal teaching context. A group of 21 Basic Education teachers attended the face-to-face training, supported by an online collaborative platform – SAPO Campus. The quantitative results showed statistically significant increases (p < .05) in the self-perception of the teachers’ media literacy skills, especially in media creation and digital identity management. The qualitative results frame a reflection on the relevance of creating digital media in students’ motivation and in the promotion of media literacy competencies. The barriers to the adoption of pedagogical practices which include media creation were also objecting to teachers’ reflection. Keywords: teacher training; game-based learning; media and information literacy; digital game creation.